Examining Factors that Affect Consumer Online Shopping Behavior: A Review Based Study (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2015)
Online shopping in India is an emerging trend for marketers to promote their merchandise in wide geographical area using internet. In 2012, E-Commerce revenue was US$ 1.6 billion but it is expected to be US$ 8.8 billion by 2016.It speaks about the success of e-commerce. Trust is an important dimension in the success of online shopping. The present study focuses on critical review of consumer behavior towards online shopping through extensive literature survey. The finding reveals that knowledge, privacy, security, perceived risk and perceived benefits are very important factors for the consumers behavior towards online shopping. Winning trust is the primary condition for enduring success in e- commerce. Finally, some useful implications have been offered to the marketers at the end.